Functional diagnostics in the training process of young biathletes - Komarova, N.; Maydokina, L.; Tsybusova, V.; Mikaeva, O.; Starostina, V. (BIO Web of Conferences, 2020)
Using modern technical means, which give information about the functional state of an athlete`s organism, can significantly increase the effectiveness of the training process control. Among such devices specialized hardware-software complex "Omega-C" is often used. The aim of the pedagogical experiment was the effectiveness substantiation of using functional diagnostics opportunities during the training process of young biathletes. 15-16 year-old biathletes were divided into two identical according to physical readiness groups. The control group trained according to typical biathlon training program with earlier planned loads. In the experimental group the volume and intensity of the training loads were selected individually and were oriented toward functional state indices of an athlete`s organism at the moment, which precedes the beginning of the work. Modern technology "Omega-C" introduction in the experimental work helped a coach and a sports doctor to monitor the quality and level of adaptive processes of 15-16 year-old athletes. It provided balance between high physical loads and health preservation. Physical state deviations registration among biathletes helped to correct timely the training process.